Peranso – Light curve and period analysis software. Issue 3 (1st March 2016) - Paunzen, E.; Vanmunster, T.
Abstract: A time series is a sample of observations of well‐defined data points obtained through repeated measurements over a certain time range. The analysis of such data samples has become increasingly important not only in natural science but also in many other fields of research. Peranso offers a complete set of powerful light curve and period analysis functions to work with large astronomical data sets. Substantial attention has been given to ease‐of‐use and data accuracy, making it one of the most productive time series analysis software available. In this paper, we give an introduction to Peranso and its functionality. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)